Gemcitabine resistance in pancreatic ductal adenocarcinoma. (November 2015) - Binenbaum, Yoav; Na'ara, Shorook; Gil, Ziv
Abstract: Pancreatic ductal adenocarcinoma (PDA) ranks fourth among cancer related deaths. The disappointing 5-year survival rate of below 5% stems from drug resistance to all known therapies, as well as from disease presentation at a late stage when PDA is already metastatic. Gemcitabine has been the cornerstone of PDA treatment in all stages of the disease for the last two decades, but gemcitabine resistance develops within weeks of chemotherapy initiation. From a mechanistic perspective, gemcitabine resistance may result from alterations in drug metabolism until the point that the cytidine analog is incorporated into the DNA, or from mitigation of gemcitabine-induced apoptosis. Both of these drug resistance modalities can be either intrinsic to the cancer cell, or influenced by the cancer microenvironment. Mechanisms of intrinsic gemcitabine resistance are difficult to tackle, as many of the genes that drive the carcinogenic process itself also interfere with gemcitabine-induced apoptosis. In this regard, recent understanding of the involvement of microRNAs in gemcitabine resistance may offer new opportunities to overcome intrinsic gemcitabine resistance. The characteristically fibrotic and immune infiltrated stroma of PDA that accompanies tumor inception and expansion is a lush ground for treatments aimed at targeting tumor microenvironment-mediated drug resistance. In the last couple of years, drugs interfering with tumor microenvironment have matured to clinical trials. Although drugs inducing 'stromal depletion' have yet failed to improve survival, they have greatly increased our understanding of tumor microenvironment-mediated drug resistance. In this review we summarize the current knowledge on intrinsic and environment-mediated gemcitabine resistance, and discuss the impact of these pathways on patient screening, and on future treatments aimed to potentiate gemcitabine activity.